Implementasi Forum An-Nisa’ dalam Meningkatkan Pemahaman Fiqih Ibadah dan Karakter Muslimah Siswi MTsN 7 Agam - Kamalasari, Dikriati; Kustati, Martin; Sepriyanti, Nana (YASIN, 2025)
The implementation of Forum Annisa at MTsN 7 Agam plays a crucial role in supporting the academic, social, and moral development of female students. This forum serves as a platform for students to share experiences and raise awareness about the importance of women’s fiqh, including reproductive health, the formation of Islamic character, and the development of social skills and leadership among Muslim women. This study employs a qualitative descriptive approach to depict the situation of Forum Annisa implementation in the field. The findings indicate that all students actively participate in the program through structured and continuous weekly meetings focused on fiqh studies, Islamic monitoring, and habituation of noble character. The positive impact of the forum is reflected in improved student understanding of worship practices and women’s fiqh, as well as the ability to apply attitudes that embody Muslimah character in daily life. Additionally, Forum Annisa contributes to building solidarity and the spirit of ukhūwah islāmiyyah among students. In conclusion, Forum Annisa is an effective strategy for enhancing religious literacy and Islamic character among female students at MTsN 7 Agam.